ALK immunohistochemistry positive, FISH negative NSCLC is infrequent, but associated with impaired survival following treatment with crizotinib. (December 2019) - Thunnissen, E.; Lissenberg-Witte, B.I.; van den Heuvel, M.M.; Monkhorst, K.; Skov, B.G.; Sørensen, J.B.; Mellemgaard, A.; Dingemans, A.M.C.; Speel, E.J.M.; de Langen, A.J.; Hashemi, S.M.S.; Bahce, I.; et al.
Highlights: Discordant ALK immunohistochemistry positive (IHC) FISH negative NSCLC occurs at low frequency. Not all locally performed ALK IHC and FISH test were centrally confirmed. Prognosis of concordant ALK IHC and FISH positive NSCLC is similar as literature. Prognosis of validated discordant ALK IHC positive FISH negative NSCLC is significantly lower. In NSCLC a positive ALK IHC screentest should be followed by ALK FISH. Abstract: Objective: Metastasized non-small cell lung cancer (NSCLC) with an anaplastic lymphoma kinase (ALK) rearrangement is usually sensitive to a range of ALK-tyrosine kinase inhibitors. ALK-positive NSCLC have been identified in pivotal phase III trials with fluorescence in situ hybridization (ALK FISH+). These tumors are also expressing the fusion product (ALK immunohistochemistry (IHC)+). However, discrepant cases occur, including ALK IHC + FISH-. The aim of this study was to collect ALK IHC + cases and compare within this group response to crizotinib treatment of ALK FISH + cases with ALK FISH- cases. Materials and methods: In this European prospective multicenter research study patients with Stage IV ALK IHC + NSCLC treated with crizotinib were enrolled. Tumor slides were validated centrally for ALK IHC and ALK FISH. Results: Registration of 3523 ALK IHC tests revealed a prevalence of 2.7% (n = 94) ALK IHC + cases. Local ALK FISH analysis resulted in 48 concordant (ALK IHC+/FISH+) and 16 discordant (ALK IHC+/FISH-) cases. Central validation revealed 37 concordant and 7 discordant cases, 5 of which had follow-up. Validation was hampered by limited amount of tissue in biopsy samples. The PFS at 1 year for ALK concordant and discordant was 58% and 20%, respectively (HR = 2.4; 95% CI: 0.78–7.3; p = 0.11). Overall survival was significantly better for concordant cases than discordant cases after central validation (HR=4.5; 95% CI= 1.2–15.9; p=0.010. Conclusion: ALK IHC + FISH- NSCLC is infrequent and associated with a worse outcome on personalized treatment. A suitable predictive testing strategy may be to screen first with IHC and then confirm with FISH instead of considering ALK IHC equivalent to ALK FISH according to the current guidelines.